13 Reasons Why: A Trigger for Teen Suicide?. Issue 1 (January 2018) - Beal, Judy A.
Abstract : The Netflix series 13 Reasons Why that depicts the story of a teenage girl who commits suicide and delivers thirteen audiotaped cassettes to classmates who played a role in her decision to kill herself has generated controversy among parents and healthcare professionals. Our pediatric nursing expert, Dr. Beal, explains why the series has become a source of concern and how it might lead to a better understanding and more open dialogue of this issue.